Evaluation of Technical and Vocational Education and Training (TVET) Programmes in Nigeria: The Kirkpatrick Model - Makinde, Wasiu Abiodun; Bamiro, Tolulope Oluwatosin (Journal of Pedagogy and Education Science, 2024)
This study aims to evaluate the Technical and Vocational, Education and Training (TVET) program in the Federal Polytechnic Ilaro using the Kirkpatrick model. The model provided a very reliable and valuable framework for evaluating education and technical training or programs with four levels of Behaviour, Learning, Reaction, and Outcome/Impact. The study population is 14290 students registered during the 2021/2022 academic session of the Institution. Krejcie and Morgam's (1974) sampling technique was adopted to have a 375 sample size for questionnaire administration purposes. The study purposively selected 375 sample sizes among the graduating classes in three out of five faculty, in which the institution was divided, to represent fifty percent of the stratification. The choice of graduating classes is to have those that are about to complete their academic program, and have gone through TVET-inclined programs for self-evaluation on the changes in their behavior, learning, reaction, and noticeable outcome-impact of TVET program on them in their immediate business environment. Descriptive and inferential statistics were adopted for analysis. The result of the findings through regression analysis produced an Adjusted R-Square of -0.005, F Statistics of 0.363, and a significant value of 0.780, which indicate that Learning, Behaviour, and Reaction did not influence the Outcome or Result of the TVET program. It was concluded that learning, reaction, and behavior were adequate in the TVET program with most respondents agreeing to the variables used to test the three levels, but had no influence on the Outcome/Impact on the improvement in the trainee’s life after the program in the Federal Polytechnic, Ilaro, Nigeria.